2021
DOI: 10.3389/fpsyg.2021.631171
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands and Job Resources of Academics in Higher Education

Abstract: Too many job demands and not enough job resources can negatively influence the well-being of employees. Currently, limited information exists surrounding the job demands and resources as experienced by academic employees in the higher education sector. Therefore, the aim of this study was to identify the job demands and job resources experienced by academic employees using qualitative methods. Semi-structured interviews were conducted with 23 academic employees, using an Interpretative Phenomenological Approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 76 publications
(110 reference statements)
1
25
0
Order By: Relevance
“…Consistent with findings from previous studies, work–home interference was considered another job demand among academics (Esteves et al, 2020 ; Naidoo-Chetty and du Plessis, 2021a ). However, only a quarter of our participants perceived this job demand to negatively affect their occupational wellbeing.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Consistent with findings from previous studies, work–home interference was considered another job demand among academics (Esteves et al, 2020 ; Naidoo-Chetty and du Plessis, 2021a ). However, only a quarter of our participants perceived this job demand to negatively affect their occupational wellbeing.…”
Section: Discussionsupporting
confidence: 88%
“…Another frequently reported job demand was work overload because of the shift to online education. Recent studies have also reported that academics have experienced workload increase during the pandemic because of digitalization in higher education (Jackman et al, 2021 ; McGaughey et al, 2021 ; Watermeyer et al, 2021 ; Naidoo-Chetty and du Plessis, 2021a ). Some of our participants reported that this had negatively affected their occupational wellbeing, but that the resource of organizational support had helped them to cope with work overload and increase their wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations